2016
DOI: 10.1039/c5ra27647k
|View full text |Cite
|
Sign up to set email alerts
|

Benzocyclobutene resin with m-carborane cages and a siloxane backbone: a novel thermosetting material with high thermal stability and shape-memory property

Abstract: A simple and effective way to synthesize carborane-containing benzocyclobutene resin with excellent performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 43 publications
(58 reference statements)
0
11
0
Order By: Relevance
“…Improvement in the thermal, mechanical, and oxidative resistance of polymers and composites after the incorporation of silsesquioxanes is known . Furthermore, materials incorporating boron clusters have a high thermal stability. ,, In this line, thermogravimetric analysis (TGA) of 3 and 4 under argon shows a thermal behavior very different from that of nonfunctionalized OVS (Figure S3). The pristine OVS shows an 82% weight loss near 290 °C, whereas both 3 and 4 undergo a very low weight loss between 350 and 600 °C, and after heating to 900 °C, around 88% of the initial weight was recovered.…”
mentioning
confidence: 94%
“…Improvement in the thermal, mechanical, and oxidative resistance of polymers and composites after the incorporation of silsesquioxanes is known . Furthermore, materials incorporating boron clusters have a high thermal stability. ,, In this line, thermogravimetric analysis (TGA) of 3 and 4 under argon shows a thermal behavior very different from that of nonfunctionalized OVS (Figure S3). The pristine OVS shows an 82% weight loss near 290 °C, whereas both 3 and 4 undergo a very low weight loss between 350 and 600 °C, and after heating to 900 °C, around 88% of the initial weight was recovered.…”
mentioning
confidence: 94%
“…Due to the high rigidity and noncoplanarity, highperformance polymer materials such as benzocyclobutene (BCB) resins with dibenzo eight-membered carbocycles proved to be responsible for the enhancement of thermal stability, low dielectric constants, low thermal expansion, and mechanical strength of the materials. 19,20 Interestingly, in 2013, we found that polyarylamides cross-linked by dibenzocyclooctadiene (DBCOD) exhibited large thermal contraction behavior. 21 Such unusual property was attributed to the reversible conformational changes from twist-boat to chair in DBCOD subunits.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Xu and Song demonstrated the thermal responsiveness of a polyhedral oligomeric silsesquioxane‐polylactides (POSS‐PLA) polyurethane network which recovers to its permanent configuration at 73 °C in 1 s . Huang et al also reported that cross‐linked benzocyclobutene resin with m ‐carborane cages and a siloxane backbone produces a heat‐responsive SMP that recovers more than 98% with recovery duration of not more than 20 s at a transition temperature of 75 °C . However, these systems may pose problems for in vivo applications due to the high T trans required to trigger shape recovery.…”
Section: Introductionmentioning
confidence: 99%